Water consumption analysis of Langat river basin - Noorazuan Md. Hashim , (Environmental Management Society, Malaysia, 2000)
Development in the southern region of Selangor especially District of Hulu Langat, Sepang as well as Kuala Langat is expected to increase in the near future with commencement of hi-tech based industrial operations and other forms of manufacturing activities and the development of new urban centres. A substantial increase of water demand is expected and in addition rapid developments of landuse activities such as urbanization and industrialization have caused a great change on the quality of water resources. Considering the above discussion, it seems that the availability of water supply will become insufficient to the State of Selangor especially Langat Basin in the near future due to rapid development and population growth. So far there has been no attempt made to study in detail the characteristics as well as the pattern of water consumption in this region. Based on this study, it is revealed that the rural population has a per capita water consumption rate as high as the urban dwellers. Considering the water demand study of Langat Basin, some of the mukims in Langat has exceeded the average of MWA water per capita consumption. These indicated that the resources were used wastefully in the domestic sector in the study area. In terms of the water supply management, most of the Langat dwellers preferred privatization of JBA in order to increase the efficiency of water services